2021
DOI: 10.1111/jcmm.16711
|View full text |Cite
|
Sign up to set email alerts
|

Tissue remodelling and increased DNA damage in patients with incompetent valves in chronic venous insufficiency

Abstract: Chronic venous insufficiency (CVI), in which blood return to the heart is impaired, is a prevalent condition worldwide. Valve incompetence is a complication of CVI that results in blood reflux, thereby aggravating venous hypertension. While CVI has a complex course and is known to produce alterations in the vein wall, the underlying pathological mechanisms remain unclear. This study examined the presence of DNA damage, pro‐inflammatory cytokines and extracellular matrix remodelling in CVI‐related valve incompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…Besides, there are some differences in younger patients (<50 years old) with venous reflux in comparison to those without venous reflux and elder patients with and without venous reflux. Our results are in agreement with previous studies in which young patients with venous reflux exhibited different molecular and tissue markers in comparison to older patients and those without venous reflux [13,15,[21][22][23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Besides, there are some differences in younger patients (<50 years old) with venous reflux in comparison to those without venous reflux and elder patients with and without venous reflux. Our results are in agreement with previous studies in which young patients with venous reflux exhibited different molecular and tissue markers in comparison to older patients and those without venous reflux [13,15,[21][22][23].…”
Section: Discussionsupporting
confidence: 93%
“…More interestingly, when we compare the total number of fibers in the venous wall according to the age, we observe that young patients with reflux show a significant increase in the elastic fibers and its diameter. These differences are in agreement to previous results observing that young patients with venous reflux exhibit an enhanced tissue remodeling, with a distinct pattern of matrix metalloproteases (MMP) activity and their endogenous tissue inhibitors of MMP (TIMPs) [13]. The enhanced elastic content in the vascular wall of young patients with reflux could indicate the need for greater dynamism in the environment of these areas of the venous wall.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have shown how proteins that are related to the MAPK pathway are expressed in vascular structures in the adventitial tunica, which could be explained by the damage that is caused by factors such as mechanical pressure. 30,37,40,41…”
Section: Discussionmentioning
confidence: 99%
“…Compression stockings, foam sclerotherapy, radiofrequency ablation, and endovenous laser therapy are available for managing VV [3][4][5][6][7][8][9][10]. However, the gold standard treatment of VV still is surgical flush ligation of the great saphenous vein and stripping incompetent veins with perforator ligation [11,12].…”
Section: Introductionmentioning
confidence: 99%